Decreas of BCL-2 Expression by Ethanol Extract of Ocinum basilicum L. Leaves in Breast Cancer Cells - Devi Nisa Hidayati; Fatimatuz Zahroh; Lina Wahyuni; Ibrahim Arifin (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2021)
Ocimum basilicum L has proven to have in vitro cytotoxic activity against breast cancer cells. Pathways that cause cell death can involve one of the proteins, which is BCL-2. This study aims to determine the decrease of BCL-2 protein expressions in breast cancer cells (T47D and MCF-7) tat are treated with the ethanol extract of Ocimum basilicum L. Ocimum basilicum L. was extracted using the maceration method with 70% ethanol solvent. The concentration of ethanol extract of Ocimum basilicum L. used to see the expression of BCL-2 protein in T47D and MCF-7 cells was 199 µg/ml and 388 µg / mL. The observation of BCL-2 protein expression is using immunocytochemical methods of T47D and MCF-7 cancer cells. The results showed that the ethanol extract of Ocimum basilicum L could reduce BCL-2 protein expression in breast cancer cells (T47D and MCF-7) at concentrations of 199 µg/ml and 388 µg/ml, respectively.